`f(x) = (3x-1)/sqrt(x)`

`or, f(x) = (3*sqrt(x)) - (1/sqrt(x))`

`or, f'(x) = (3/2)*(1/sqrt(x)) + (1/2)*(1/x^(3/2)) `

`or, f'(x) = {(1/2)*(1/sqrt(x))*[3 + (1/x)]`

` `

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now